2020
DOI: 10.1108/ijchm-10-2019-0869
|View full text |Cite
|
Sign up to set email alerts
|

Why should errors be tolerated? Perceived organizational support, organization-based self-esteem and psychological well-being

Abstract: Purpose On the basis of conservation of resources theory, the purpose of this paper is to propose a framework linking an organizational factor, organizational error tolerance, with employees’ psychological well-being through gains of psychological resources: perceived organizational support (POS) and organization-based self-esteem (OBSE). Design/methodology/approach Across three-wave data collected from 220 hotel frontline employees, this study tests the proposed model using structural equation modeling thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 82 publications
(98 reference statements)
3
63
1
1
Order By: Relevance
“…Similarly, previous studies also support our results [ 85 , 86 , 87 ]. This relationship is supported by organizational support theory [ 88 ]. So, the above discussion proves that organizational support and employee well-being reduce a toxic workplace environment and increase the level of employee engagement.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, previous studies also support our results [ 85 , 86 , 87 ]. This relationship is supported by organizational support theory [ 88 ]. So, the above discussion proves that organizational support and employee well-being reduce a toxic workplace environment and increase the level of employee engagement.…”
Section: Discussionmentioning
confidence: 65%
“…More importantly, personal control often serves as a buffer against stressors or negative life events, and thus, the research has shown that individuals with higher levels of personal control have fewer health problems and higher levels of wellbeing when encountering a crisis (Greenaway et al, 2015). Further still, ample studies have demonstrated similar results in the hospitality workplace (Wang et al, 2020;Xu et al, 2020;Yoon and Yoon, 2019).…”
Section: Linking Stressors To Well-being and Career Change Intentionmentioning
confidence: 99%
“…As argued by Ariza-Montes et al (2018), if the hospitality industry fails to promote the well-being of its workforce, the industry may soon lack enough committed workers. Therefore, hospitality scholars have frequently examined how work stressors influence the well-being of hospitality workers (Ariza-Montes et al, 2018;Haver et al, 2019;Hsu et al, 2019;Wang et al, 2020).…”
Section: Linking Stressors To Well-being and Career Change Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results provide clear evidence that when an employee has included their job in their ideal self, employees feel more satisfied and more engaged by the existential challenges of life (i.e., PWB). Additional to previous research relating psychological well-being to different factors and antecedents such as emotional intelligence (Kamboj and Garg, 2021) and organizational error tolerance (Wang et al, 2020), the ideal self comes to create a more comprehensive picture of what leads to employee well-being.…”
Section: The Ideal Self and Employee Engagementmentioning
confidence: 99%